Facile preparation of Ti3C2Tx sheets by selectively etching in a H2SO4/H2O2 mixture - Tian, Zhengshan; Tian, Hao; Cao, Kesheng; Bai, Suzhen; Peng, Qinlong; Wang, Yabo; Zhu, Qiuxiang (Frontiers in Chemistry, 2022)
MXenes and MXene-based composite materials have potential applications in a wide range of areas due to their unique physical and chemical characteristics. At present, it is still a major challenge to develop a simple, safe and efficient route to prepare MXenes without using fluorinated etchants. Herein, we design a facile method to prepare Ti3C2Tx MXene sheets by selective etching Ti3AlC2 powders in an aqueous diluted H2SO4 solution with H2O2 as oxidant. In a system of H2SO4 and H2O2, an aqueous H2SO4 solution with a concentration of 6 mol/L is a strongly acidic medium with no volatility, and 30 % H2O2 acts as a strong green oxidizer without harmful by-products. The experimental process is safe and convenient to operate in a beaker under a water bath of 40 °C. The etching process can be completed in 1 h under the air atmosphere conditions. The experimental results confirmed that the etched Ti3AlC2 powders can be successfully separated into Ti3C2Tx nanosheets under ultrasound treatment without using any intercalation agent. The relevant etching mechanism is maybe attributed to the synergy effect of H2SO4 and H2O2, which triggers sequential selective etching of Al layers from the Ti3AlC2 phase. It maybe provides a new green way to prepare MXene-based materials without using toxic HF or HF-containing etchants. Keywords: Ti3AlC2 powders, Ti3C2Tx sheets, H2SO4/H2O2 mixture, selective etching, HF-containing etchants